Islamic Education Planning Based on Local Wisdom for Strengthening Students' Identity and Life Skills - Dasep Supriatna; Ahmad Hapidin; Syamsuri Syamsuri (STKIP Pesisir Selatan, 2026)
Contemporary Islamic education faces significant challenges due to the dominance of standardized curricula that often overlook students’ sociocultural contexts. This condition may create a disconnect between Islamic values taught in schools and students’ lived experiences, thereby weakening identity formation and limiting the development of practical life skills. This study aims to examine Islamic education planning based on local wisdom and its role in strengthening students’ identity and life skills. Employing a qualitative approach with a case study design, the research was conducted at an Islamic boarding school in West Sumatra, Indonesia, which is deeply rooted in the Minangkabau philosophy of Adat basandi syarak, syarak basandi Kitabullah. Data were collected through in-depth interviews, classroom observations, focus group discussions, and curriculum document analysis, involving school leaders, teachers, students, and community elders. The data were analyzed thematically using Vygotsky’s sociocultural theory as the analytical framework. The findings reveal that the integration of local wisdom into Islamic education planning functions as an effective cultural mediation tool in the learning process. This integration contributes to the harmonious strengthening of students’ religious and cultural identity and enhances the development of context-specific life skills, such as social deliberation, conflict resolution, and community responsibility. The study concludes that Islamic education planning grounded in local wisdom is a relevant and strategic approach to fostering meaningful, contextual, and transformative learning experiences.